2017
DOI: 10.9790/1959-0601045462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Implementing Intra-Aortic Balloon Pump Teaching Program on Critical Care Nurse's knowledge and Practice

Abstract: Background: Intra-aortic balloon pump (IABP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This study results were in the same line with (Thapa and Neupane, 2018) who conducted a study to assess the impact of teaching program on nurses knowledge concerning intra-aortic balloon pump (IABP) implantation therapy for coronary artery bypass grafting patients at selected hospitals in Dehradum and found that the majority of the studied nurses had reported adequate level of knowledge regarding IABP which increased after intervention. Additionally, Elsay et al (2016); Mahgoub and Abd El-Hafez (2017);and Shini et al (2018), who documented that there was significant difference between preprogram and post program knowledge with a fact of an increased level after implementing their programs than before.…”
Section: Discussionmentioning
confidence: 99%
“…This study results were in the same line with (Thapa and Neupane, 2018) who conducted a study to assess the impact of teaching program on nurses knowledge concerning intra-aortic balloon pump (IABP) implantation therapy for coronary artery bypass grafting patients at selected hospitals in Dehradum and found that the majority of the studied nurses had reported adequate level of knowledge regarding IABP which increased after intervention. Additionally, Elsay et al (2016); Mahgoub and Abd El-Hafez (2017);and Shini et al (2018), who documented that there was significant difference between preprogram and post program knowledge with a fact of an increased level after implementing their programs than before.…”
Section: Discussionmentioning
confidence: 99%